Normal to y=f(x) , Mathematics

If the normal to y=f(x) makes an angle of pie/4 with y-axis at (1,1) , then f''(x) is eqivalent to?

Ans) The normal makes an angle 135 degree with the x axis.

also f ''(1)=1 .....[since the tan pie/4=1=slope of normal]

Also the graph passes by (1,1) so

f(1)=1,and already proved....

f ''(1)=1

Both these are possible only if  f(x)= [x^2 + 1] / 2

hence  f '''' (x) = 1 

 

 

Posted Date: 4/5/2013 1:36:08 AM | Location : United States







Related Discussions:- Normal to y=f(x) , Assignment Help, Ask Question on Normal to y=f(x) , Get Answer, Expert's Help, Normal to y=f(x) Discussions

Write discussion on Normal to y=f(x)
Your posts are moderated
Related Questions
Wendy has 5 pairs of pants and 8 shirts. How many different combinations could she form with these items? Multiply the number of choices for each item to find out the number of

THE FIRST AND THIRD TERM OF A G.P ARE 8 AND 18 RESPECTIVELY AND THE COMMON RATIO IS POSITIVE.FIND THE COMMON RATIO

WHAT IS PRECALC

Seriation :  You have read about a preschooler's ability to order. Ordering a set of objects means to arrange them in a sequence according to some rule. This arrangement could be

On dividing p(X)=5x^(4)-4x^(3)+3x^(2)-2x+1 by g(x)=x^(2)+2 if q(x)=ax^(2)+bx+c, find a,b and c.

Example:  find out the slope of equations and sketch the graph of the line.                         2 y - 6x = -2 Solution To get the slope we'll first put this in slope

using the g.e matrix, how can you turn an unattractive product to be attractive

Find the volume of a cylinder of radius r and height h. Solution : Here, as we mentioned before starting this illustration we actually don't require using an integral to get t

Solve the subsequent quadratic equation: Solve the subsequent quadratic equation through taking the square roots of both sides. 3x 2 = 100 - x 2 Solution: Step 1

The length of the sides of a triangle are 2x + y/2 , 5 x/3 + y + 1/2  and 2/3 x  + 2y + 5/2. If the triangle is equilateral. Find its perimeter. A ns: 2x + y/2 = 4x + y